A hybrid method for overlapping speech detection in classroom environment. Issue 1 (21st July 2017) - Jiang, Dazhi; Chen, Yifei; Garg, Akhil
Abstract: Classroom discourse, which is a major composition of classroom, contains a slew of useful information such as providing the feedback to the teachers may lead to an improvement of the teaching quality. Generally, the classroom discourse can be divided into four categories/activities: teacher discourse, student discourse, quiet, and discussion. The automatic classification of activities provides a practical way to deal with the classroom discourse. However, the recognition of the discussion activity (a kind of overlapping speech) poses a great challenge to the treatment of the classroom discourse analysis. Therefore, in this paper, a new hybrid method based on the silence distribution and Independent Component Analysis (ICA) was proposed for the detection of overlapping speech. The results were found to be satisfactory and in good agreement with an experimental data. Based on these experimental results, the performance of the speaker segment of classroom event can be efficiently analyzed.